The Concept Of Islamic Identity And Its Importance For Muslim Youth - Gaya, Shahbaz; Ahmad, Nadzrah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Muslim youth face a variety of threats in preserving and developing their Islamic identity. The most significant threats include peer pressure, assimilation, materialism, corrupt desires, religious doubt, loss of religion in society, and Islamophobia. This study aims to derive the main components of an Islamic identity from the Qur’ān towards the development and preservation of Muslim youth. An inductive approach was used to analyse the Qur’ān in search of marking the significant characteristics of the Islamic Identity. It was found that the Islamic identity is defined by its salient characteristics of a fundamental belief system, a united link to a global ummah, and an encompassing nature, making it inherently influential in all aspects of a Muslim’s private and public life. These components deal specifically with the major threats faced by Muslim youth in preserving their Islamic identity. It was also found that the Islamic identity serves as an anchor in establishing and preserving the faith of young Muslims. Finally, if this identity is not preserved it may lead to consequences such as the corruption of faith and creed and engagement in oppression and sin. It is through identifying, understanding, and developing the Islamic identity, that Muslim youth can successfully preserve their faith, even during the most challenging of times.